Management of Juvenile Nasopharyngeal Angiofibroma in a Referral Hospital in West Java, Indonesia - Yussy Afriani Dewi; Ifiq Budiyan Nazar (Althea Medical Journal, 2020)
Background: Juvenile nasopharyngeal angiofibroma (JNA) is a fibrovascular tumor originating from the supero-posterior area of the sphenopalatine foramen. This tumor is histologically benign, but is clinically malignant because JNA has potentially destructive spread extending to the skull base and the cranium. The aim of the study was to evaluate the management of JNA in Dr. Hasan Sadikin General Hospital Bandung, a referral hospital in West Java.Methods: This was a descriptive retrospective study using medical record data of JNA patients during the period of 2011-2018. The stage of JNA was designated, based on the FISCH classification.Results: There were112 JNA cases, consisting of 99% male and 1% female. Most of them (97%) were aged 10-20 years old (median16 years old). The chief complaints were nasal obstruction (46%) and recurrent epistaxis (36%). Most of the JNA stage was stage II (43%). Major feeding vessel of JNA was from an internal maxillary artery (IMAX) and ascending pharyngeal artery (28%). Preoperative management was equal for ligation and embolization. The complication of embolization was local pain (75%). The most surgical technique performed was the transpalatal approach (41.36%). Blood loss in a different stage in JNA surgery with embolization was less than surgery with ligation. There were patients (10%)with residual disease after 6 months follow-up.Conclusions: JNA is essentially a disease of the adolescent males. The management of JNA patients is surgery, mostly using transpalatal technique. Preoperative embolization of JNA is a safe procedure, minimizes intraoperative blood loss, decrease the incidence of residual or recurrence, and shortening the duration of the surgery.